National Fiqh Discourse in the Digital Public Sphere: A Case Study of TVMu’s Dialektika Program - Umar, Tia Muthiah; Atie Rachmiatie; Kiki Zakiah; Makroen Sanjaya (Komunikator, 2025)
The discourse of national fiqh within Indonesia’s digital public sphere has become increasingly prominent with the rise of digital media, particularly as religious discussions intersect with issues of nationality, pluralism, and civic identity. This study examines how the concept of national fiqh is articulated through TVMu’s Dialektika program, which functions as a digital deliberative arena for Islamic communication. Using a qualitative case study approach, the research analyzes four selected episodes and incorporates insights from interviews with the editorial team, supported by NVivo-assisted coding (open, axial, and selective). The findings indicate several key dimensions: the strategic selection of credible communicators; message framing that emphasizes justice, pluralism, and the integration of Islamic principles with Pancasila; the use of multiplatform distribution through television, YouTube, and social media; a dual audience strategy addressing both Muhammadiyah members and the wider Muslim public; and a discursive shift from provocative narratives toward ethical deliberation. Overall, Dialektika functions as a moderate Islamic medium that not only delivers normative da'wah but also fosters an inclusive deliberative public sphere, reinforcing the relevance of national fiqh in sustaining social cohesion and shaping civic Islam. The novelty of this study lies in its integration of national fiqh discourse, digital media analysis, and deliberative public sphere theory while positioning the Lasswell model solely as a technical mapping framework